Human capital for digital economy modernization - V. Y. Afanasyev; E. P. Grabchak; M. A. Korytny; S. V. Mishcheryakov; A. V. Cherezov (Управление)
The article outlines the scientific approaches to the formation of digital technologies of the ecosystem of professional education and management of the formation of human capital for the real sector of the Russian economy. It has been proposed to highlight specific competences as training units (quantums), digitize them, create a level classifier and build an ordering system, a system of choice used for order fulfillment, a continuous (from general education to professional education for a given position) professional education system based on individual educational trajectories with well-defined (digitized) parameters and focused investments in human capital. Using the formed systems, it has been proposed to provide digital modernization of the main didactic processes with guaranteed achievement of specific diagnosed learning outcomes in accordance with the order.For new competencies it is possible to develop ontological models of employee professional activities. Herewith it is planned to solve several important tasks, including the development and adoption of a general concept of continuous professional education, the selection and classification of didactic units for specific professions, the development and introduction of a classification system for educational organizations according to their levels of competence, the development and introduction of a system for qualifying teachers, formation of a system of educational trajectories (necessary competencies) for business, development of pedagogical technologies standards that guarantee the achievement of results (the right people - in the right place - at the right time). It has been offered to select several branches of the real sector of the economy for the implementation of pilot projects with the subsequent dissemination of experience throughout the Russian economy.